Perceptions of selected interior designer on the relevance of the existing subjects in the Philippine interior design licensure exam to the professional interior design practice - Chua, Kiros Christian K. (College of Home Economics, University of the Philippines Diliman, 2022)
This exploratory qualitative study sought to investigate the perceptions of selected licensed interior designers on the relevance of the existing subjects in the Philippine Interior Design licensure exam to current interior design practice. Data gathering was conducted through online video-conferencing applications which enabled one-on-one interviews with thirteen (13) respondents who were chosen through snowball sampling method, following the selection criteria which requires each respondent to be a licensed interior designer in the Philippines with at least three (3) years of professional interior design work experience. Thematic analysis was then conducted in order to analyze the data, with key ideas and concepts from each interview being highlighted and sorted into broader themes. Results show that majority of the respondents found the seven subjects of the licensure examination to be either “Relevant” or “Very Relevant”, with the subjects of “Interior Construction and Utilities” and “Professional Practice and Ethics” garnering the most number of responses, indicating them as “Very Relevant”. Varying responses were given regarding how each subject was relevant or applied in the experience of each respondent. Different overarching factors that affected the relevance and application of each subject area surfaced. These factors included: 1) Client Needs and Priorities, 2) Client Preferences, Trends, and Awareness, 3) Restrictions or Requirements by a Building or Institutional Administration, 4) Role of Allied Professionals, Suppliers, and Contractors, 5) Job Description and Scope of Work, 6) Risk and Sales, and 7) Industry-specific or Project-specific Terms and Practices. Further studies are recommended to look into other factors that may have a bearing on the perceptions of licensed interior designers on the relevance of the abovementioned subjects in the Interior Design licensure exam to the professional practice of Interior Design.